Coronary Angiographic Findings in Survivors of Sudden Cardiac Arrest at Nicvd Karachi - Bilawal Adrani, Vashu Mal, Sanaullah Sheikh, Asif Ali, Vickee Kumar Mamtani, Rizwan Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The most recent guidelines advocate an immediate coronary angiography [1] for those who have survived a cardiac arrest and are still exhibiting electrocardiographic indications of ischemia. Recovered cardiac patients who don't show signs of ongoing ischemia may nonetheless need an emergency angiography, according to the same recommendations. Conventional ECG is ineffective in diagnosing if coronary culprit lesions are present during an angiography, according to earlier study [2]. As a result, some believe that all patients who are resuscitated after a cardiac arrest should undergo an urgent cardiac catheterization. [3]. Objective: To determine the frequency of coronary angiographic findings in survivors of sudden cardiac arrest. Materials and methods: We included all patients who satisfied the study's criteria and visited the NICVD in Karachi for treatment. After a thorough explanation of the study's procedures, risks, and benefits, participants agreed to participate. The results of coronary angiography were recorded for each patient. The form at the end contained all of the information that had been acquired and was used electronically for research purposes. Results: Mean ± SD of age was 51.4±10.6 years. In distribution of gender, 142 (67.6%) were male while 68 (32.4%) were female. left anterior descending (LAD) as noted in 104 (49.5%) patients, left circumflex artery (LCX) in 31 (14.8%), 52 (24.8%) had right coronary artery (RCA) while left main artery (LMA) was found in 23 (10.9%) patients. Conclusion: It is to be concluded that left anterior descending noted as most common coronary angiographic finding followed by right coronary artery and left circumflex artery. Epidemiological and research data should be expanded by further studies to validate the current findings.